Medicolegal aspects of digestive endoscopy: Results of a Chilean national survey - Corsi, Oscar; Fuenzalida, María Jesús; Vargas, José Ignacio; Silva, Verónica; Figueroa, Maximiliano; Prato, Juan Andrés; Künsemüller, Andrea; Espino, Alberto (Endoscopy International Open, 2025)
Medical professional liability (MPL) is a significant concern for gastrointestinal physicians, yet there are limited data available from Latin America. We aimed to assess frequency of complaints and lawsuits related to digestive endoscopy among gastrointestinal endoscopists in Chile and to identify associated factors.An online survey collected sociodemographic data, information about endoscopy unit characteristics, and MPL-related experiences. Invitations were sent to 525 gastrointestinal endoscopists in Chile between August and September 2022. Associations between categorical variables were analyzed using the Chi-square test.In total, 140 endoscopists participated (response rate: 26.7%). Mean age was 48.8 years; 68.6% were gastroenterologists, 70.7% were male, and 95% had MPL insurance. Written complaints were reported by 55% of participants, with an average of 1.5 complaints per year. The most common causes were procedure costs, adverse events (AEs), and sedation issues. Colonoscopy was the procedure most frequently associated with complaints (63.2%). Complaints related to AEs included perforation (48.7%), hemorrhage (23.7%), pancreatitis (21.1%), and death (13.2%). Factors associated with complaints included years of endoscopic practice (P = 0.047), therapeutic procedures (P < 0.001), and patient satisfaction assessments (P = 0.048). Of respondents, 14.5% reported at least one lawsuit. Factors associated with lawsuits included age (P = 0.0047), male gender (P = 0.0033), Chilean nationality (P = 0.0257), therapeutic procedures (P = 0.004), and patient satisfaction assessments (P = 0.002).Gastrointestinal endoscopists are frequently exposed to complaints and lawsuits. Key factors include procedure costs, AEs, sedation practices, years of experience, type of endoscopic procedure, and communication. Proactive strategies to address these factors could mitigate medico-legal risks and improve patient outcomes.
Keywords: Quality and logistical aspects; Quality management; Performance and complications; Training